Room air constituent concentrations from use of electronic nicotine delivery systems and cigarettes using different ventilation conditions - Michael J. Oldham (Nature Portfolio, 2021)
Abstract To assess potential exposure of non-users to exhaled constituents from pod and cartridge electronic nicotine delivery systems (ENDS) products, an environmental clinical study was conducted with (n = 43) healthy adult smokers. Room air concentrations of 34 selected constituents (nicotine, propylene glycol, glycerin, 15 carbonyls, 12 volatile organic compounds, and 4 trace metals) and particle number concentration (0.3 to 25 µm) were compared from use of two ENDS products and conventional cigarettes using room ventilations representative of a residential, an office or a hospitality setting over a 4-h. exposure period. Products used were JUUL ENDS, Virginia Tobacco flavor (Group I), VUSE Solo, Original flavor (Group II) (5.0 and 4.8% nicotine by weight, respectively) and subjects’ own conventional cigarettes (Group III). Cumulative 4-h room air sampling and particle counting were performed during prescribed (Groups I and II) and ad libitum product use (all Groups). Conventional cigarette use resulted in significantly more constituents detected and higher 4-h cumulative constituent concentrations compared to use of the ENDS products tested, except for the predominant ENDS ingredients, propylene glycol and glycerin. Use of conventional cigarettes also resulted in greater total particle number concentration than either prescribed or ad libitum use of either of the ENDS used in this study.